Effectiveness of Infant Massage on Strengthening Bonding and Improving Sleep Quality - Hartanti, Ainurrizma Tri; Salimo, Harsono; Widyaningsih, Vitri (Indonesian Journal of Medicine, 2019)
Background: Baby massage is the oldest and most popular touch therapy known to mankind, which is also the art of health care and treatment that has been practiced for centuries. This study aims to determine the effect of infant massage on bonding attachments between mother and baby and the quality of infant sleep.Subjects and Method: This was experimental study with Randomized Controlled Trial (RCT) design conducted in five health centers in Ponorogo Regency, East Java in March to April 2019. The total sample was 120 mothers and infants aged 3 to 6 months divided between massage groups (treatment) and not massage (control) based on The dependent variable of this study was bonding attachment and sleep quality. The independent variable in this study was infant massage. Data collection was using questionnaires and checklists. This study used the Mann-Whitney testResult: Infant massage effectively increased bonding attachment (effect size = 6.19; p <0.001), increased infant sleep duration (effect size= 2.79, p <0.001), decreases the number of baby awakened (effect size = -2.78; p <0.001), decreased duration awakened (effect size= -0.80; p= 0.001), Conclusion: Baby massage effectively increased bonding attachment and sleep duration, and effectively decreased the number of awakenings and the duration of awakening.Keywords: baby massage, bonding attachment, sleep qualityCorrespondence: Ainurrizma Tri Hartanti, Public Health Postgraduate Program, Universitas Sebelas Maret. Jl. Ir. Sutami 36 A, Surakarta 57126, Central Java. Email: ainurrizma.th@yahoo.co.id. Mobile: 085784939555Indonesian Journal of Medicine (2019), 4(2): 165-175https://doi.org/10.26911/theijmed.2019.04.02.10